Future direction of language education in Malaysia - Mat Daud, Nuraihan (Penerbitan Universiti Kebangsaan Malaysia (UKM), 2010)
The study was an investigation of how tertiary level language education evolved in Malaysian universities since 1966. In line with the National Higher Education Strategic Plan (2007), the study seeks to profile the range of languages, linguistics, and literature courses and their strengths and unique features across all language departments of different universities in Malaysia. The study compiled a comprehensive database of language-based programmes which fall into either of the three categories namely language proficiency courses, language programmes, and programmes for the teaching of languages. Data examining students' rate of employment after graduating from languages, linguistics and/or literature undergraduate and postgraduate degree programmes in Malaysia revealed that English and Arabic language majors were the most easily employed while graduates majoring in other languages still face issues with gaining employment in the relevant work sectors in Malaysia. This was ascertained from the various published market survey results and tracer studies across time by the Ministry of Higher Education. The study also highlights Malaysia's lack of experts in areas of language studies, linguistics and literature and how languages, linguistics and literature education need to be further improved and aligned with the current needs of the country so as to contribute to nation building and the further development of the Malaysian economy. The study concludes by highlighting the need for a better recognition of the value of language education and the identification of avenues for further development of language education in Malaysia.